Tajikistan : Review of Public Expenditures on Health - World Bank (Washington, DC, 2014)
This policy note is part of the World Bank's Programmatic Public Expenditure Review (PER) work program for FY2012-2014. The PER consists of a series of fiscal policy notes, which aim at providing the Government of Tajikistan with recommendations to strengthen budgetary processes and analysis. This policy note, the second in the series, examines public expenditures on health in Tajikistan. After an introductory section, the note describes the institutional and administrative structure of the health sector. Section 3 presents health outcomes and health care utilization indicators. Section 4 describes health financing in Tajikistan and presents the main options to expand fiscal space for health. Section 5 reviews the health financing and organizational reforms implemented in Tajikistan. Section 6 provides the main conclusions: 1) despite progress, health sector outcomes are mixed in Tajikistan and utilization pattern of health services is characterized by significant inequalities; 2) public spending on health is relatively low and skewed towards hospitals rather than outpatient care; 3) the hospital sector is characterized by oversupply of beds, avoidable inpatient admissions, low occupancy rates, and excessive average length of stay; 4) an increase in public health expenditures since 2000 was largely driven by the expanding wage bill, while other expenditures had been compressed; 5) public health expenditures show a regressive incidence, with the distribution of inpatient care more pro-rich than outpatient care; 6) the large reliance on out-of-pocket produces a high incidence of catastrophic spending; 7) a number of health financing and organizational reforms have been initiated since 2000, but the scope and coverage is still limited; and 8) the overall prospect for increasing fiscal space for health in Tajikistan are positive, with rationalization of both the overall budget and the public health delivery system.